Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Kontekstual Berdasarkan Kriteria John Watson Ditinjau Dari Perbedaan Gender - Andhita Cahyo Sujiwo, Dimas; Ramadanti, Della Asisca; Marsidi, Marsidi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2025)
This research aims to analyze students' errors based on John Watson's criteria in the material of congruence and congruence of flat shapes. This research approach is qualitative with a descriptive type. Students are given a test to identify mistakes made when solving questions. Interviews were conducted to find out the causes of the types of errors they made when completing the test. This research used 8 selected subjects, namely class IX students of MTs Sunan Giri Pakusari. Analysis is carried out by calculating the expression of each indicator and interpreting it based on Watson's criteria. In the research results, female students made more mistakes in inappropriate procedures, with a percentage of 22.5%, and missing conclusions, with a percentage of 25.8%. Meanwhile, male students made more mistakes in missing data, with a percentage of 19.3%, and missing conclusions, with a percentage of 25.8%. Keywords: Error Analysis, Contextual Questions, John Watson Criteria, Gender